An optimal sensor location based protection scheme for DER-integrated hybrid AC/DC microgrid with reduced communication delay. (June 2022) - Rameshrao, Awagan Goyal; Koley, Ebha; Ghosh, Subhojit
Abstract: In spite of the advantages, the acceptance of hybrid microgrid has been hindered due to the complexity of the protection task. With increased number of DERs (Distributed Energy Resources) and loads in the network, the placement of sensors in every bus for proper monitoring and protection is often not economical both in terms of sensor installation cost and the cost associated with communication infrastructure. Transmission of high volume of sensor information through the communication network demands high bandwidth for reduced communication delay. In this regard, a low-cost protection scheme for hybrid microgrid with optimal sensor placement and immunity against converter faults has been proposed. The issues related to sensor placement and increased impact of communication delay of the reported techniques has been addressed by identifying a set of optimal sensor locations for network observability. The scheme based on Wavelet Packet Decomposition (WPD) and ensemble classifier has been extensively validated in terms of the optimality of identified sensor locations, minimization of communication delay and accuracy of the protection scheme.